Integrating concentrating PVs in biogas upgrading. (July 2018) - Tian, Zhenyu; Hao, Yong; Li, Wenjia; Campana, Pietro Elia; Li, Hailong; Yan, Jinyue; Jin, Hongguang
Abstract: Biogas produced from anaerobic digestion processes has been considered as an important alternative to natural gas and plays a key role in the emerging market for renewable energy. By removing CO2, biogas can be upgraded to vehicle fuel. Chemical absorption is one of the widely used upgrading technologies, which advantages include high purity and low loss of biomethane. However, chemical absorption usually suffers from the high consumption of thermal energy, which is required by the regeneration of the solvent. Aiming at achieving a more sustainable and efficient biomethane production, this work proposed a novel system, which integrate concentrating photovoltaic/thermal hybrid (C-PV/T) in the upgrading of biogas. Due to the ability to produce electricity and heat simultaneously and efficiently, C-PV/T can provide the demands of both the electricity and heat. By doing dynamic simulation of the energy production of C-PV/T, the technical feasibility of such a system is analyzed. Based on the design to meet the heat demand of solvent regeneration, without energy storage, the produced heat can cover 17% of the heat demand of the solvent regeneration, but 51.1% of the electricity demand; meanwhile, 140.3 MWh excess electricity can be sold for one year.